Effectiveness of low-level laser therapy and topical steroid therapy in the management of oral lichen planus - Omar H Soliman; Eisa M Hegazy; Eman M Abdulhady; Asem M Kamel; Mahmoud A Attia; Nicola Baldini; Hayder R Abdulbaqi; Ahmed M Fekry; Rahma G Mostafa; Ahmed M Hussein (Journal of Baghdad College of Dentistry)
Background: Corticosteroids are the most common treatment for oral lichen planus, a long-term immune-related condition, which is considered the most effective treatment. Photobiomodulation is a viable alternative treatment that can successfully treat various pathological disorders by relieving pain, decreasing inflammation, and facilitating tissue healing. Unlike steroid medications, photobiomodulation does not have any associated disadvantages. This study aimed to assess and compare the effects of topical application of 0.1% triamcinolone acetonide and photobiomodulation on erosive oral lichen planus. Methods: A randomized controlled clinical trial was conducted in this investigation, which involved 20 patients who were suffering from erosive oral lichen planus. The control group (n= 10) was administered a 0.1% topical solution of triamcinolone acetonide 3 times daily and a miconazole oral gel once daily, for 4 weeks. The patients in the second group (n = 10) engaged in laser therapy twice a week for 8 sessions over 4 weeks, utilizing a 980 nm diode laser with an output power of 300 mw. Pain and clinical scores of patients were evaluated at the start and 4 weeks postoperatively.  Results: Both groups were not significantly different from one another, and both had substantial improvements in pain and clinical scores. Conclusions: Low-Level Laser therapy showed potential as a therapeutic approach for treating erosive oral lichen planus, offering an alternative to steroid therapy without the associated adverse effects.